Validation of game-experience-learning based youth football coaching model to optimize skills and character - sulistiyono, sulistiyono; Sugiyanto, Sugiyanto; Kristiyanto, Agus; Purnama, Sapta Kunta (Journal Humanitarian Responsibilities, Education & Sport Sciences (JHRESS), 2020)
This study aims to develop an effective football coaching model to improve the playing skills and character of young athletes aged 9-12 by using Borg & Gall’s research and development design. This research was carried out through the stages of preliminary research, identifying the theoretical foundations for the model, designing the model, developing games and drill activities as the contents of the framework, and validating the developed model. The data were collected by means of depth interviews, literature studies, and expert validation with delphy techniques. The collected data is reduced, verified, analyzed and inferred. Based on the analysis of the collected data, it is determined that the training model based on experience learning games is feasible to be continued at the small-scale field test stage.